2022
DOI: 10.31181/110722105k
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Wear Parameters for Duplex-TiAlN Coated MDC-K Tool Steel Using Fuzzy MCDM Techniques

Abstract: The present work evaluates the effects of different tribological process parameters on the measured responses such as hardness, coefficient of friction, surface roughness, wear mass loss and wear depth of duplex-TiAlN coated MDC-K tool steel material. The considered tribological process parameters are load, sliding velocity, and sliding distance. A full factorial design with 27 experimental runs is employed and based on the response values, an optimal combination of the tribological process parameters is subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Various other researchers also applied FLT approach for analysing the performance aspects, on the basis of reliability parameters of process industries-Robotic system (Sharma et al, 2012a); Paper mill (Sharma et al, 2012b); Power generating unit (Panchal & Kumar, 2016a); Water treatment plant (Panchal & Kumar, 2016b);Chlorine plant (Panchal et al, 2019); Chemical industry ; Dairy industry (Gopal & Panchal, 2023c). Moreover IFS find wider application with Multi Criteria Decision Making Approach (MCDM) approach also.Researchers have applied IFS based MCDM approaches in various fields-Healthcare services (Ecer & Pamucar, 2021);Logistics centre selection (Pamučar & Ćirović, 2015); Bidder selection (Pamučar et al, 2017);Tribological process (Kumar et al, 2022);Firing positions' locations selection (Jokić et al, 2021);Barrier selection in supply chain management (Biswas & Das, 2020).…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Various other researchers also applied FLT approach for analysing the performance aspects, on the basis of reliability parameters of process industries-Robotic system (Sharma et al, 2012a); Paper mill (Sharma et al, 2012b); Power generating unit (Panchal & Kumar, 2016a); Water treatment plant (Panchal & Kumar, 2016b);Chlorine plant (Panchal et al, 2019); Chemical industry ; Dairy industry (Gopal & Panchal, 2023c). Moreover IFS find wider application with Multi Criteria Decision Making Approach (MCDM) approach also.Researchers have applied IFS based MCDM approaches in various fields-Healthcare services (Ecer & Pamucar, 2021);Logistics centre selection (Pamučar & Ćirović, 2015); Bidder selection (Pamučar et al, 2017);Tribological process (Kumar et al, 2022);Firing positions' locations selection (Jokić et al, 2021);Barrier selection in supply chain management (Biswas & Das, 2020).…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Similarly, according to the above tables, the pattern "if -then" is valid for all other cases. For future studies, the suggested method can be improved by the fuzzy approach of [24][25][26].…”
Section: Adjusting the Parameters Of Pid For Avr Loopmentioning
confidence: 99%
“…Frequency Deviation (pu) Remark 5. Te suggested method can be developed by using new fuzzy systems, and combining with new control systems [27], new optimization techniques [26], and new decision making methods [28].…”
Section: Simulationsmentioning
confidence: 99%
“…Multi Criteria Decision Making (MCDM) method is an effective technique for selecting optimal parametric combination [29][30][31]. The MCDM approach entails normalising the decision matrix, then computing the assessment value, and the combination with the highest assessment value is considered optimal [32]. Somu et al optimised EDM parameters using the VIKOR optimization approach [33], Srinivasan et al optimised welding parameters with the GRA optimization technique [34], and Kannan et al optimised LBM with the TOPSIS optimization technique [35].…”
Section: Introductionmentioning
confidence: 99%